Isotope Effects in Plasmonic Photosynthesis - Yu, Sungju; Jain, Prashant K. (Angewandte Chemie - International Edition, 2020)
The photoexcitation of plasmonic nanoparticles has been shown to drive multistep, multicarrier transformations, such as the conversion of CO2 into hydrocarbons. But for such plasmon-driven chemistry to be precisely understood and modeled, the critical photoinitiation step in the reaction cascade must be identified. We meet this goal by measuring H/D and 12C/13C kinetic isotope effects (KIEs) in plasmonic photosynthesis. In particular, we found that the substitution of H2O with D2O slows hydrocarbon production by a factor of 5–8. This primary H/D KIE leads to the inference that hole-driven scission of the O−H bond in H2O is a critical, limiting step in plasmonic photosynthesis. This study advances mechanistic understanding of light-driven chemical reactions on plasmonic nanoparticles.
Keywords: Hydrocarbon production; Isotope effect; Kinetic isotope effects; Light driven; Limiting step; Multi carrier; Photoinitiation; Reaction cascades; catalysis; CO2 reduction; hot electrons; localized surface plasmon resonance; nanoparticles